Internalization of Islamic Moderation Values in Building a Civilization of Love and Tolerance - Karimullah , Suud Sarim; Faizin , Mu’adil; Islami , Aufa (LPPPM STAI Darul Hikmah Bangkalan, 2023)
The purpose of this research is to obtain information about the pattern of internalization of Islamic moderation values in building a civilization of love and tolerance by harbouring all the differences that can create hostility and disharmony amid a pluralistic social life. This research is library research because all the data used as material for conducting studies comes from texts or manuscripts that have become library collections using qualitative research methods and analyzed with the nature of descriptive analytic studies. The results of this study state that Islamic moderation values in their implementation in social life as an effort to prevent various extremist, fundamentalist, liberal and radical understandings that are very far from Islamic teachings, which are full of love and tolerance. Love and tolerance are important provisions in forming civilization in a harmonious religious life without any conflict due to diversity. Love can also foster harmony in religious, national and state life, thus creating peace in society. Love makes a person have good morals who always want peace so that he always pleases others in every word and behaviour. Meanwhile, with better tolerance, constructive and efficient dialogue will be built, which can foster religious attitudes and an atmosphere that is more open, plural, and inclusive.